Wild common bean in the central valley of Costa Rica: Ecological distribution and molecular characterization = Frijol silvestre en el Valle Central de Costa Rica: distribución ecológica y caracterización molecular - González Torres, Rosa Inés; Araya Villalobos, Rodolfo; Gaitán Solís, Eliana; Debouck, Daniel G. (2004)
Wild common bean in the Central Valley of Costa Rica: ecological distribution and molecular characterization. This work offers an update on the distribution of wild common bean in Costa Rica. its ecology and molecular characterization. To date 22 populations have been discovered in four watersheds around the Central Valley, usually in man-made habitats (often sides of coffee plantations), under varying conservation status (from protected to threatened). Molecular characterization indicates that the wild common bean belong to the Mesoamerican gene pool. Different markers indicate an increased genetic diversity in some wild populations, and allow to hypothesize the presence of gene flow and introgression from cultivated materials.